Survey of the Attitude to, the Knowledge and the Practice of Contraception and Medical Abortion in Women Who Attended a Family Planning Clinic - Umashankar K.M.; Dharmavijaya M.N.; Jayanta Kumar D.E.; Kala K.; Abed Gulab Nagure; Ramadevi (Journal of Clinical and Diagnostic Research, 2013)
Objective: To assess the attitude to, the knowledge and practice of contraception and medical abortion in women attending the family planning clinic at the mvj medical college , hosakote , Bangalore, India. Materials and Methods: Between 1st of August, 2011 and 31st of July, 2012 200 women attending family planning clinic of the mvj medical college, hosakote, Bangalore India of which 105 requested for medical termination of pregnancy (mtp), 95 for family planning advice, were interrogated on a structured questionnaire. The age of women ranged in between 20-45 years, 71 (35.5%) were illiterate, 30 (15%) had primary school education and 99 (49.5%) had diplomas from high school and above. Patients were grouped into low and high socio-economic status according to modified kuppuswamy socio-economic status scale: (i). upper class, (ii). Upper middle class, (iii). Middle class, (iv). Lower middle class, (v). lower class.consent of both husband and wife was taken. They were counseled about the various contraceptives available and allowed to choose whichever suited them best. Results: Among the 200 women 85 (42%) did not use contraception; 51 (25.5 %) were on the barrier method; 49 (18.31%) used intrauterine devices (iud); 12 (6%) used oral pills and and 3 (1.5%) used other methods. the request for mtp was on grounds of unplanned pregnancy in 55.25% cases or failure of contraception in 44.7%. there was no eugenic indication of the women, 3 (1.5%) had heard about emergency contraceptives, however none had used them; 20 (10%) had heard of medical abortion and 12 (6%) had previously undergone mtp with satisfaction. the various methods of contraception accepted by the women post abortion were ocps by 11 (10.47%), iuds by 54 (51.5%) and female sterilization by 26 (24.71%). in the other group, 23 (24.2%) had iuds removed and reinserted; 37.8% had iuds inserted; 26 (27.36%) women underwent sterilization operation; and 6 (6.31%) had iuds removed opting for pregnancy. statistical analysis was done using spss software (Chicago) with χ2 test taking p value of 0.05 as significant. Conclusion: There is lack of awareness of emergency contraception and medical abortion in the women community under study.